Evolutionary Trends of Perkinsozoa (Alveolata) Characters Based on Observations of Two New Genera of Parasitoids of dinoflagellates, Dinovorax gen. nov. and Snorkelia gen. nov. - Reñé, Albert; Alacid, Elisabet; Ferrera, Isabel; Garcés, Esther (Frontiers in Microbiology, 2017)
Parasites are one of the ecologically most relevant groups of marine food webs, but their taxonomic and biological complexity hampers the assessment of their diversity and evolutionary trends. Moreover, the within-host processes that govern parasitoid infection, development and reproduction are often unknown. In this study, we describe a new species of a perkinsozoan endoparasitoid that infects the toxic dinoflagellate Dinophysis sacculus, by including observations of its morphology, ultrastructure, life-cycle development and phylogeny. The SSU rDNA sequence and main morphological features were also obtained for a second parasitoid species infecting the bloom-forming dinoflagellate Levanderina fissa. Phylogenetic analyses including the sequences obtained show that all known Perkinsozoa species infecting dinoflagellates cluster together. However, sequences of Parvilucifera prorocentri and those obtained in this study cluster at the base of the clade, while the rest of Parvilucifera representatives form a separated highly-supported cluster. These results, together with differing morphological characters like the formation of a germ-tube, the presence of trichocysts, or the heterochromatin presence in zoospores nucleus justify the erection of Dinovorax pyriformis gen. nov. et sp. nov., and Snorkelia prorocentri gen. nov. et comb. nov. (=Parvilucifera prorocentri). The morphological features and phylogenetic position of these parasitoids represent ancestral characters for the Perkinsozoa phylum, and also for Dinozoa clade, allowing the inference of the evolutionary framework of these Alveolata members.